Defense of Quintus Ligarius - Marco Tulio; Henao, Rafael (Estudios de Filosofía, 1994)
You have in your hands the translation of what, for many, is Cicero’s best speech. The circumstances were very difficult. With the war between Caesar and Pompey, the full Roman nobility supported this seasoned general determined to fight armed with a fledgling.